Social Network Analysis of Integrated Medical Services for Hypertension – Using District Hospitals of Shanghai as a Model - Chen Ziyou; Li Junshan; Li Fen; Lu Yuanan (Journal of Hypertension and Cardiology, 2020)
Objective To examine the current linkage between different medical services for hypertension patients for enhanced integration among medical service systems. Methods A total of 18 hospitals and community medical centers from a district of Shanghai were enrolled for social network analysis which covered emergency visits and hospitalization records of 171,177 outpatients with hypertension. Stata software was used for data preprocessing and UCINET software was used for network analysis of medical service providers to quantify and visualize the network tightness and the
Keywords: Social network analysis